Evaluating the use of oral pre-exposure prophylaxis among pregnant and postpartum adolescent girls and young women in Cape Town, South Africa - Khadka, Nehaa; Gorbach, Pamina M.; Nyemba, Dorothy C.; Mvududu, Rufaro; Mashele, Nyiko; Javanbakht, Marjan; Nianogo, Roch A.; Aldrovandi, Grace M.; Bekker, Linda-Gail; Coates, Thomas J.; Myer, Landon; Joseph Davey, Dvora L. (Frontiers in Reproductive Health, 2023)
Background: Adolescent girls and young women (AGYW) have elevated risk of incident HIV in South Africa. Despite growing availability of daily oral pre-exposure prophylaxis (PrEP) for HIV prevention, little is known about PrEP use during pregnancy and postpartum serviced at antenatal care(ANC) facility.We used data from HIV-uninfected pregnant women aged 16-24 in Cape Town, South Africa enrolled in the PrEP in pregnancy and postpartum (PrEP-PP) cohort study at their 1 st ANC visit. Using the PrEP cascade framework, the outcomes were PrEP initiation (prescribed TDF-FTC at baseline), continuation (returned for prescription) and persistence(quantifiable tenofovir diphosphate[TFV-DP] in dried blood). Exposures were baseline HIV risk score (0-5), condomless sex, >1 sexual partner, partner living with HIV/ unknown serostatus, laboratory diagnosed STI, hazardous alcohol use before pregnancy (AUDIT≥3). We used logistic regression to examine associations between HIV risk and PrEP adjusting for a priori confounders.Results: Of 486 pregnant women, 16% were "adolescents" (16-18 years) and 84% were "young women" (19-24 years). ANC initiation was later for adolescents than young women (median=28 weeks [20-34] vs 23 weeks [16-34], P=0.04). About 41% had a STI diagnosis at baseline. Overall, 83% of AGYW initiated PrEP at 1 st ANC; PrEP continuation was 63% at 1 month, 54% at 3 months and 39% at 6 months. About 27% consistently continued PrEP through 6 months and 6% stopped and restarted. AGYW with a higher HIV risk (score≥2 vs ≤1) had increased odds of continuing PrEP (aOR, 1.85 [95% CI, 1.12-3.03]) through 6 months adjusting for potential confounders. Barriers to PrEP continuation included being postpartum (vs. pregnant) and having lower sexual risk factors. TFV-DP was detected among 49% of AGYW and 6% had daily adherence to PrEP at 3 months.Conclusions: AGYW had high oral PrEP initiation, but just over one-third continued on PrEP by 6 months. Pregnant AGYW who had more HIV risk (condomless sex, sex frequency, and STIs) were more likely to continue on PrEP through postpartum period. Pregnant AGYW who are pregnant and postpartum require counseling and other support including community delivery, peer support to improve their effective PrEP use through postpartum period.